Isoconversional Kinetic Analysis of Thermally Stimulated Processes in Polymers - Vyazovkin, Sergey; Sbirrazzuoli, Nicolas (Macromolecular rapid communications., 2006)
Isoconversional kinetic analysis involves evaluating a dependence of the effective activation energy on conversion or temperature and using this dependence for making kinetic predictions and for exploring the mechanisms of thermally stimulated processes. The paper discusses major results obtained by the authors in the area of the isoconversional analysis of polymer kinetics over the past decade. It provides a brief introduction to isoconversional methods and surveys the impact made by isoconversional analysis in several application areas that include kinetic predictions, thermal degradation, crosslinking (curing), glass transition, and glass and melt crystallization. It is concluded that isoconversional analysis has been used broadly and fruitfully because it presents a fortunate compromise between the single‐step Arrhenius kinetic treatments and the prevalent occurrence of processes whose kinetics are multi‐step and/or non‐Arrhenius. An isoconversional method applies the Arrhenius equation to a narrow temperature region, ΔT related to a given extent of conversion.